Quality of Life and Events in the First Year of Life. Results from the Prospective Copenhagen Birth Cohort 1959?61 - Søren Ventegodt; Trine Flensborg-Madsen; Niels Jørgen Andersen; Mohammed Morad; Joav Merrick (The Scientific World Journal)
The objective of this paper was to explore the association between diverse factors occurring during the first year of a child?s life and the quality of life later as an adult. The design was a prospective cohort study based on material from the Copenhagen Birth Cohort 1959–61 with 7,222 participants and two sets of questionnaires used: one by a physician during the child's first year and one by the ?adult child? 31–33 years later. The results showed that a mother's attitude towards her pregnancy, unsuccessful abortions, and/or institutionalization left a permanent trace on the child, since these children, as adults, have a quality of life 3% below the average. Meningitis during the first year of life resulted in a quality of life 11.7% below the average, while other illnesses or accidents did not have an effect. The largest associations were found with psychomotor development, where “walking with support” showed a difference of 14.2% in overall quality of life between the fastest and slowest group. Generally, diet is not correlated with quality of life, however, we find a small, but essential, correlation between the quality of life of the adult and the early cessation of suckling (4%). Full-time institutionalization during the first year of life showed a connection with the quality of life of the adult (7.1%). It is concluded that our quality of life, health and ability as adults are primarily determined by what we ourselves choose to do with our lives as young people and as adults - and only to a marginal degree determined by factors related to our background. This suggests that we as adults have a great freedom to achieve a good life despite our experiences in the beginning of life.